Simulated Vibrational Analysis of Internally Fixated Femur to Monitor Healing at various Fracture Angles. (2017) - Chiu, W.K.; Ong, W.H.; Russ, M.; Fitzgerald, M.
Abstract: Finite element analysis has been performed to investigate the feasibility of using modal analysis to determine whether an internally fixated femur is healing. Two types of fixation are investigated, an intramedullary nail(IM) and a plate style fixation. Both are installed on a Sawbone artificial femur by a surgeon which is then 3D scanned to create the finite element model. Modal analysis of these two fixations will predict the stiffness of the system using each fixation and also identify which type of modes are most sensitive to healing. Various cut orientations are also modelled to test their influence on natural frequency of the femur.